Position specific morphological characteristics of top-level male handball players - Srhoj, V.; Marinovic, M.; Rogulj, N. (Collegium Antropologicum, 2002)
With the aim of determining the common morphological features of senior male handball players and of analyzing their specificities i.e. the probable variation between the four playing positions (back court players, wings, pivots, goalkeepers), 25 anthropometric measures were applied to the sample of 49 players, members of three top-quality handball teams. The basic descriptive parameters were calculated and then an analysis of variance and a cluster analysis were performed. A mesomorphic, athletic body- type was obtained with a marked longitudinal skeleton dimensionality, but also with a balanced ratio between the skeletal system and muscle mass and with low values of subcutaneous fat tissue. Back court players and goalkeepers are superior in terms of outstanding skeletal dimensions and circumferences. Line players, i.e. wings and pivots, have somewhat lower longitudinal measures, whereas pronounced voluminosity and a slightly higher fat tissue value differentiate pivots from players in other positions. Cluster analysis revealed a greater homogeneity in the morphological profiles of the samples of line players (wings and pivots) than in the profiles of backs or goalkeepers. The obtained position-related differences in morphological characteristics of players suggest that the experienced players from the sample were earlier successfully subjected to the selection process and oriented to a particular playing position because of the observed correspondence between their body-type and specific kinesiological demands of the position in question. Therefore, in top-quality team-handball it would be recommendable to select players whose morphological profiles are as compatible as possible with positional specificities in the demand for the game.